Contracts as a barrier to entry when buyers are non-pivotal - Özlem Bedre-Defolie; Gary Biglaiser (European School of Management and Technology (ESMT), 2015)
We analyze whether the use of breakup fees by an incumbent might induce an inefficient allocation of consumers and possibly foreclose efficient entry where buyers are non-pivotal (infinitesimal) and have to pay switching costs if they switch from the incumbent to an entrant. When the entrants are competitive, in the unique equilibrium the incumbent induces the efficient outcome, so there is no inefficient foreclosure. When there is a single entrant, the incumbent cannot deter the entry if it is not allowed to use a breakup fee. In the equilibrium of this case there might be too much or too little entry depending on the entrant's cost advantage versus the highest level of switching costs. When the incumbent can use a breakup fee in its long-term contract, in the unique equilibrium the incumbent forecloses the entrant by a sufficiently high breakup fee. This result does not depend on the level of switching costs or the entrant's efficiency advantage. We extend the result to a situation where consumers do not face switching costs, but they get a lower match value from the entrant's product than the incumbent's. In this case the results differ only when there is a single entrant. There are no inter temporal effects without breakup fees and if the incumbent is allowed to use breakup fees, it forecloses the entrant if and only if the entrant's cost advantage is sufficiently low compared to the highest switching cost. All results are robust to allowing the incumbent to offer a spot price.
urn:nbn:de:101:1-201507247796; More recent version: http://hdl.handle.net/10419/149865
Keywords: 650